Stakeholder dynamics and sustainable waste management in peri-urban settings: a case study of actor interactions in Indonesia - Mukhlis, Imam; Fauzan, Slamet; Rahmawati, Farida; de Silva, Saliya; Melati, Inaya Sari (Frontiers in Sustainable Cities, 2025)
This study investigates stakeholder dynamics within the TPS3R (Reduce, Reuse, Recycle Waste Processing Site) waste management program in Tulungagung Regency, East Java, Indonesia. TPS3R, a community-driven waste management initiative, aims to mitigate waste generation’s environmental and health impacts by promoting waste segregation, recycling, and circular economy practices. Tulungagung Regency was chosen for its representative peri-urban characteristics, including rapid urbanization and the coexistence of urban and rural attributes. The study employs the MACTOR (Matrix of Alliances and Conflicts: Tactics, Objectives, and Recommendations) methodology to analyze interactions among 15 key stakeholders, encompassing government officials, local community members, and environmental advocates. Findings highlight that effective program implementation relies on strengthened leadership collaboration, resolving political tensions, and increasing community participation. While existing studies often focus on urban or rural settings, this research addresses a notable gap by exploring stakeholder dynamics in peri-urban areas, emphasizing the unique challenges and opportunities of such settings. Evidence from literature and primary data underscores the importance of integrating high-level leadership and grassroots participation for sustainable waste management. This study contributes to the field by presenting an original, localized examination of peri-urban stakeholder interactions, offering actionable recommendations to enhance the success of similar initiatives globally.